2021
DOI: 10.1177/02698811211009794
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation and relapse with paliperidone palmitate three-monthly for maintenance of schizophrenia: Two year follow-up of use in clinical practice

Abstract: Background: The use of antipsychotic long-acting injections (LAI) aims to reduce risk of relapse and hospitalisation in patients with schizophrenia compared with oral medication. Paliperidone palmitate is currently the only LAI that can be administered at three-monthly intervals for maintenance treatment of schizophrenia. Aim: This prospective study aimed to evaluate relapse and continuation in licensed use of paliperidone palmitate three-monthly (PP3M) over a 2-year follow-up in clinical practice. Method: Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Paliperidone palmitate is currently the only LAI that can be administered at 3 monthly intervals for maintenance treatment of schizophrenia. They found that overall, most patients initiated on PP3M in this prospective clinical setting study continued treatment and remained well (Wallman et al, 2021). This is concordant with previous RCTs of PP3M and with naturalistic studies.…”
Section: Antipsychotics the Heartland Of Clinical Psychopharmacology?supporting
confidence: 88%
“…Paliperidone palmitate is currently the only LAI that can be administered at 3 monthly intervals for maintenance treatment of schizophrenia. They found that overall, most patients initiated on PP3M in this prospective clinical setting study continued treatment and remained well (Wallman et al, 2021). This is concordant with previous RCTs of PP3M and with naturalistic studies.…”
Section: Antipsychotics the Heartland Of Clinical Psychopharmacology?supporting
confidence: 88%
“…Other naturalistic studies have been conducted, but as previously discussed, there are many issues that hinder their comparability with the present findings. [9][10][11] The study with the most comparable methodological design to the present one is that reported by Wallman et al 13 and Clark et al 14 in which relapse rates of 7.2% and 10.8% were found during the 2 years following PP3M initiation, which is much lower than the relapse rate herein reported. A first explanation for these lower rates than that obtained here are the different definitions of relapse used.…”
Section: Therapeutic Advances In Psychopharmacologysupporting
confidence: 59%
“…This is an important consideration given that Ferraro et al 12 found a very high relapse rate of 35.7% within a sample of FEP patients, a population in which comorbid psychiatric diagnoses are the norm rather than the exception. Unfortunately, rates of comorbid diagnoses were not reported by Wallman et al 13 nor by Clark et al, 14 making it impossible to compare their population with that of the present study on that crucial aspect.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…26 At 2 years, 42% of 225 patients TherapeuTic advances in psychopharmacology prescribed monthly paliperidone LAI continued their medication and 60% of 111 patients prescribed 3-monthly paliperidone LAI continued with their medication. 27,28 The authors of the 3 monthly LAI study attributed the better rates to patients having been previously stable on monthly Paliperidone. We add to this information, reporting OLAI continuation at 2 years as 51% of 88 patients and at 60 months as 31% of 70 patients.…”
Section: Discussionmentioning
confidence: 99%